MARKETING STRATEGY OF SMALL AND MEDIUM ENTERPRISES (MSMES) IN INCREASING SALES OF BROWN SUGAR IN SEI SILAU, ASAHAN REGENCY - Safrida (CV. Radja Publika, 2023)
This research is in the form of descriptive research, where this research aims to find out what strategy is appropriate for a business actor to use. By using SWOT analysis, this research was conducted by business actors working in the food industry, namely the Brown Sugar SMEs in Sei Silau Village, Asahan District. data obtained from the results of primary data, secondary data. Several test methods are steps from the SWOT analysis test, including using the IFAS Matrix, EFAS Matrix, and SWOT diagrams. The result value of the IFAS matrix test (2.59) is used as the X axis (horizontal) in the SWOT diagram and the result value from the EFAS matrix test (2.80) is used as the Y axis (vertical) in the SWOT diagram. SWOT results explain that the company is in area IV, where in these areas it illustrates that the internal factors of MSME business actors are weak. The results of the SWOT analysis which are described using the SWOT diagram show that the MSME business conditions are in quadrant IV, which means that the Brown Sugar MSMEs in Sei Silau Village, Asahan Regency are in a Defensive position and the strategy that can be implemented is a marketing strategy that can implemented by the Brown Sugar MSME business actors in Sei Village, Asahan Regency is an Aggressive Strategy, namely business actors must be able to develop existing strengths and increase and maintain existing opportunities.